Draft Fifth Five-Year Plan West Bengal - Planning Commission (Planning Commission, 1973)
The economy of West Bengal is now poised for a big change in its structure, composition, and rate of growth. the central aim for analysing the current socio-economic situation is to identify the main determinants of this change and to find out whether, how, and to what extent these determinants may be influenced by planned action. This analysis will thus attempt to formulate the basis of the specific objectives of the Fifth Plan and the strategy for achieving these objectives
Government of West Bengal, Development and Planning Department